Composite diaphragm for alkaline electrolyzed water and preparation method and application thereof
Patent Information
- Application Number
- CN202611092139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-30
AI Technical Summary
其中,纳米二氧化锆(ZrO2)凭借其优异的耐强碱腐蚀性、良好的亲水性和热稳定性,被公认为聚合物基复合隔膜中最具潜力的增强相之一;然而,现有的纳米ZrO2填充聚砜复合隔膜仍存在明显不足:单一尺寸的纳米ZrO2在聚合物基体中极易团聚,分散均匀性差,导致隔膜局部缺陷增多;更为关键的是,这类隔膜无法从根本上解决离子传导率与机械强度、气密性之间的矛盾,高填料填充量虽然有利于提升离子传导,却往往以牺牲膜的柔韧性和气体阻隔性为代价
本发明提供的碱性电解水用复合隔膜,通过将特定粒径(30-80nm)和特定钇掺杂浓度(6-10mol%)的纳米氧化锆颗粒,以高填充量(占聚砜质量50%-70%)均匀分散于聚砜基体中,并利用相转化工艺形成贯穿指状孔结构,实现了氧空位工程与纳米粒径的协同增效。一方面,Y3+对Zr4+的晶格取代在氧化锆内部引入高浓度氧空位,极大地增加了颗粒表面羟基密度,赋予隔膜超亲水特性(接触角≤30°)和优异的离子传导能力;另一方面,30-80nm的小粒径颗粒在聚合物基体中形成高密度界面网络,为氢氧根离子提供了快速的界面传输路径,而贯穿指状孔结构则大幅降低了离子在隔膜厚度方向的传质阻力;更为重要的是,平均孔径3-5nm的小孔结构保证了高气体阻隔性(泡点压力≥0.6bar),高孔隙率(60%-70%)则确保了高电解液吸持率,两者的协同优化从结构上突破了传统隔膜离子传导率与气密性相互制约的矛盾;此外,均匀分散的钇掺杂纳米氧化锆颗粒构建了稳定的物理屏障,有效阻挡强碱对聚砜主链的侵蚀,实现了30天碱失量≤0.2%的优异耐碱稳定性;上述综合性能使得本发明的复合隔膜在500mA/cm²电流密度下电解电压≤1.70V,并能稳定运行375小时以上,表现出卓越的电解效率和长期运行可靠性,且整个制备过程仅涉及常规的相转化法,无需复杂设备,易于工业化放大。
Smart Images

Figure CN123005451A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alkaline water electrolysis for hydrogen production, specifically to a composite membrane for alkaline water electrolysis, its preparation method, and its application. Background Technology
[0002] In alkaline water electrolysis for hydrogen production, the diaphragm plays a crucial role in isolating hydrogen and oxygen, preventing a mixed explosion, while allowing hydroxide ions to pass through to form a complete circuit. The diaphragm performance directly determines the purity of the produced gas and the energy consumption of electrolysis. Currently, research on alkaline water electrolysis diaphragms mainly focuses on improving mechanical strength, ionic conductivity, gas barrier properties, and alkali resistance. Polysulfone (PSF / PSU) materials have become an ideal matrix for composite diaphragms due to their excellent film-forming properties, mechanical strength, and chemical stability. However, the intrinsic hydrophobicity of polysulfone severely limits ion conduction efficiency, leading to high surface resistivity and increased energy consumption during electrolysis. Although its hydrophilicity can be improved through chemical modification methods such as sulfonation and grafting, these methods are often complex, costly, and may sacrifice the chemical stability of the matrix.
[0003] To improve the hydrophilicity and ion conductivity of polysulfone membranes, inorganic fillers are commonly used for physical blending modification. Among them, nano-zirconium dioxide (ZrO2) is recognized as one of the most promising reinforcing phases in polymer-based composite membranes due to its excellent resistance to strong alkali corrosion, good hydrophilicity, and thermal stability. However, existing nano-ZrO2-filled polysulfone composite membranes still have significant shortcomings: single-sized nano-ZrO2 is prone to agglomeration in the polymer matrix, resulting in poor dispersion uniformity and an increase in local defects in the membrane. More importantly, these membranes cannot fundamentally resolve the contradiction between ion conductivity, mechanical strength, and gas tightness. Although high filler content is beneficial for improving ion conductivity, it often comes at the cost of sacrificing membrane flexibility and gas barrier properties.
[0004] Studies have shown that introducing trivalent yttrium ions (Yttrium ions) into the ZrO2 lattice... 3+ Doping can be performed by substituting Zr. 4+ Simultaneously, oxygen vacancies are generated, thereby constructing efficient oxygen ion transport channels within the crystal lattice, forming the so-called ion highway. Taking a typical 8 mol% yttrium-stabilized zirconium oxide (YSZ) as an example, its oxygen vacancy concentration can reach approximately 2 × 10²¹ per cubic centimeter, which theoretically can greatly promote the transport of hydroxide ions in the membrane. However, existing technologies have not yet synergistically applied the oxygen vacancy effect of yttrium-doped zirconium oxide (Y-ZrO2) with the particle size control strategy of nanoparticles to alkaline water electrolysis composite membranes, resulting in the potential of Y-ZrO2 not being fully utilized. How to prepare a membrane with low surface resistivity, high airtightness, and excellent alkali resistance through the synergy of filler design and membrane structure control is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a composite membrane for alkaline water electrolysis, its preparation method and application.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This application provides a composite diaphragm for alkaline water electrolysis, comprising: Polysulfone matrix; Yttrium-doped zirconium oxide nanoparticles dispersed in the polysulfone matrix; the yttrium element in the yttrium-doped zirconium oxide nanoparticles is in the form of trivalent yttrium ions (Y). 3+ Form doping is introduced into the zirconium dioxide lattice, replacing some of the tetravalent Zr in the zirconium dioxide lattice. 4+ The ions form a solid solution, wherein the average particle size of the yttrium-doped zirconium oxide nanoparticles is 30 nm to 80 nm, wherein the molar content of yttrium is 6% to 10%, and the mass of the yttrium-doped zirconium oxide nanoparticles is 50% to 70% of the mass of the polysulfone matrix; The composite membrane has a finger-like pore structure, with the finger-like pores extending throughout the membrane thickness direction. The average pore size of the composite membrane is 3nm–5nm, the porosity is 60%–70%, the surface water contact angle is ≤30°, and the surface resistivity in a 30% (w / w) KOH aqueous solution at 80°C is ≤0.10 Ω·cm. 2 .
[0007] Optionally, the yttrium-doped zirconium oxide nanoparticles have an average particle size of 50 nm, a doping molar content of yttrium of 8%, and a mass of yttrium-doped zirconium oxide nanoparticles that is 60% of the mass of the polysulfone matrix.
[0008] Optionally, the composite diaphragm has a mass loss rate of ≤0.2% after being soaked in a 30% KOH aqueous solution at 60°C for 30 days; the electrolysis voltage is ≤1.70V under the conditions of a current density of 500mA / cm², a temperature of 60°C, and an electrolyte of 30% KOH aqueous solution, and the voltage fluctuation is ≤0.1V after continuous electrolysis for 375h under the same conditions.
[0009] Optionally, the composite diaphragm has a bubble point pressure ≥0.6 bar, a tensile strength ≥1.8 MPa, and an elongation at break ≥30%.
[0010] A method for preparing the above-mentioned composite membrane includes the following steps: S1, dissolve polysulfone resin in N-methylpyrrolidone to obtain a polysulfone solution; S2, add polyvinylpyrrolidone to the polysulfone solution, mix and dissolve to obtain a polymer mixed solution; S3, add yttrium-doped nano-zirconia powder to the polymer mixture, disperse it evenly and remove bubbles to obtain a casting solution; S4, the casting liquid is scraped onto the substrate to form a liquid film, and then the substrate with the liquid film is immersed in a coagulation bath to carry out phase transformation to obtain a wet film; S5, the wet membrane is washed and dried to obtain the composite diaphragm.
[0011] Optionally, in step S1, the mass ratio of the polysulfone resin to N-methylpyrrolidone is 1:5 to 10.
[0012] Optionally, in step S2, the mass ratio of polyvinylpyrrolidone to polysulfone resin is 0.8 to 1.2:1.
[0013] Optionally, in step S3, the mass ratio of the yttrium-doped nano-zirconia powder to the polysulfone resin is 0.5 to 0.7:1.
[0014] Optionally, in step S4, the coagulation bath is a mixture of deionized water and N-methylpyrrolidone, with a volume ratio of water:NMP=8:2 to 9.5:0.5; the immersion time is 1 to 4 hours.
[0015] Application of a composite membrane in an alkaline water electrolysis hydrogen production device.
[0016] Compared with the prior art, this application has the following beneficial effects: The composite membrane for alkaline water electrolysis provided by this invention achieves synergistic effects of oxygen vacancy engineering and nanoparticle size by uniformly dispersing nano-zirconia particles of a specific particle size (30-80 nm) and a specific yttrium doping concentration (6-10 mol%) in a polysulfone matrix at a high loading (50%-70% of the polysulfone mass) and forming a through-finger pore structure using a phase transformation process. On the one hand, Y... 3+ For Zr 4+The lattice substitution introduces a high concentration of oxygen vacancies within the zirconia, significantly increasing the hydroxyl density on the particle surface and endowing the membrane with superhydrophilic properties (contact angle ≤30°) and excellent ion conductivity. On the other hand, the small-diameter particles (30-80 nm) form a high-density interfacial network within the polymer matrix, providing a rapid interfacial transport path for hydroxide ions, while the through-hole finger-like pore structure significantly reduces the mass transfer resistance of ions along the membrane thickness. More importantly, the small-pore structure with an average pore size of 3-5 nm ensures high gas barrier properties (bubble point pressure ≥0.6 bar), while the high porosity (60%-70%) ensures high electrolyte adsorption. The synergistic optimization of the two components structurally overcomes the contradiction between the ion conductivity and airtightness of traditional membranes. In addition, the uniformly dispersed yttrium-doped nano-zirconia particles construct a stable physical barrier, effectively blocking the erosion of the polysulfone backbone by strong alkalis, achieving excellent alkali resistance with an alkali loss of ≤0.2% after 30 days. The above comprehensive performance enables the composite membrane of this invention to operate stably for more than 375 hours at an electrolysis voltage of ≤1.70V at a current density of 500mA / cm², demonstrating excellent electrolysis efficiency and long-term operational reliability. Moreover, the entire preparation process only involves conventional phase inversion methods, requiring no complex equipment and is easy to scale up industrially. Attached Figure Description
[0017] Figure 1 This is a cross-sectional SEM image of the composite diaphragm prepared in Example 1 of the present invention.
[0018] Figure 2 This is a planar SEM image of the composite membrane prepared in Example 1 of the present invention.
[0019] Figure 3 EDS elemental distribution map (showing Zr and Y elements) of the composite membrane prepared in Example 1 of the present invention.
[0020] Figure 4 This is a water contact angle test diagram of the composite membrane prepared in Example 1 of the present invention. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] In the following examples and comparative examples, polysulfone resin (PSF) was purchased from Solvay, model P-1700; polyvinylpyrrolidone (PVP) was K30 with an average molecular weight of approximately 40,000; N-methylpyrrolidone (NMP) was analytical grade; Y-doped nano-zirconia powder and undoped nano-ZrO2 powder were commercially available products, and powders with different particle sizes and doping concentrations could be obtained by controlling the preparation process; unless otherwise specified, all other reagents used were analytical grade.
[0023] Scanning electron microscopy (SEM) and electronic spectroscopy (EDS) were performed using a Hitachi SU8010 field emission scanning electron microscope. Water contact angle was measured using an OCA20 video contact angle meter. Porosity was determined using the wet-dry weight method with deionized water as the wetting medium. Alkali absorption rate was calculated by weighing the diaphragm after soaking it in 30wt% KOH solution for 4 hours. Sheet resistivity was tested using the AC impedance method at 80℃ and 30wt% KOH. Tensile strength and elongation at break were tested according to GB / T1040.3-2006 standard. Bubble point pressure was determined using the bubble point method. Alkali stability was evaluated by immersing the diaphragm in 30wt% KOH solution at 60℃ for 30 days and calculating the mass loss rate (alkali loss). Electrolytic performance was tested in a dual-electrode electrolytic cell with 30wt% KOH as the electrolyte, at 60℃, and a current density of 500 mA / cm², and the electrolysis voltage was recorded.
[0024] This application provides a composite diaphragm for alkaline water electrolysis, comprising: Polysulfone matrix; Yttrium-doped zirconium oxide nanoparticles dispersed in the polysulfone matrix, wherein the average particle size of the yttrium-doped zirconium oxide nanoparticles is 30 nm to 80 nm, wherein the molar content of yttrium doping is 6% to 10%, and the mass of the yttrium-doped zirconium oxide nanoparticles is 50% to 70% of the mass of the polysulfone matrix; The composite membrane has a finger-like pore structure that extends throughout the membrane's thickness. The average pore size of the composite membrane is 3 nm to 5 nm, its porosity is 60% to 70%, its surface water contact angle is ≤30°, and its surface resistivity in a 30% (w / w) KOH aqueous solution at 80°C is ≤0.10 Ω·cm. 2 .
[0025] Specifically: Regarding the polysulfone matrix, its function is to serve as the skeletal material of the diaphragm, giving the diaphragm basic mechanical strength and film-forming properties; the present invention selects polysulfone (PSF / PSU) resin because it has excellent film-forming properties, mechanical strength and chemical corrosion resistance, making it suitable as the matrix material for alkaline water electrolysis diaphragms; specifically, commercially available polysulfone resin (Sowe P-1700 type) is used, with an amount of 9.8g.
[0026] Regarding yttrium-doped zirconia nanoparticles, dispersed in a polysulfone matrix, they are the core functional component that imparts hydrophilicity, ion conductivity, and alkali resistance to the membrane; yttrium-doped zirconia nanoparticles are the industry-standard yttrium-stabilized zirconia (YSZ) solid solution powder; yttrium is present in the form of Y... 3+ Ionic solid solution doping is performed in the ZrO2 crystal lattice, replacing the Zr in the lattice. 4+ The site forms a homogeneous single-phase solid solution without free Y₂O₃ impurities; such as Figure 3 The surface distribution of EDS elements confirms that Y and Zr elements are uniformly distributed within the nanoparticles, thus corroborating the existence of lattice doping.
[0027] Furthermore, the charge balance mechanism in this application is the charge compensation mechanism in yttrium-stabilized zirconium oxide (YSZ) solid solution, as detailed below: To maintain the electroneutrality of the crystal, oxygen vacancies are introduced into the lattice accordingly; in the defect chemistry model, an oxygen vacancy can be regarded as the removal of an O atom from the lattice. 2- For an ion, relative to a perfectly electrically neutral lattice, the vacancy is equivalent to the introduction of an effective positive charge of +2.
[0028] Each Y 3+ Replace Zr 4+ Missing +1, two jointly missing +2; this +2 effective positive charge exactly compensates for the two Y... 3+ Replace two Zr 4+ The resulting charge deficiency achieves overall charge balance in the system; the defect reaction equation is as follows:
[0029] in: This represents the incorporated yttrium oxide; Representing two Ys 3+ Ions occupy Zr 4+ lattice positions; This represents the creation of one oxygen vacancy with two units of effective positive charge; This means that three oxygen ions normally occupy oxygen positions in the crystal lattice.
[0030] This demonstrates that the entire crystal lattice maintains strict electrical neutrality both macroscopically and locally.
[0031] Furthermore, in the actual solid solution formation process, oxygen atoms do not disappear into the vacuum, but rather achieve equilibrium through oxygen lattice reconstruction introduced by the dopant Y₂O₃ and oxygen rearrangement within the system; however, from the perspective of equivalent charge analysis in defect chemistry, compared to the complete ZrO₂ lattice, an oxygen atom is missing at each oxygen vacancy. 2−The ion, therefore, the defect is equivalent to having a +2 positive charge; this analytical method belongs to the standard theoretical model in the field of solid-state electrochemistry, and the charge balance equation... That is, it is derived from this model.
[0032] This charge compensation mechanism directly determines the performance advantages of the diaphragm of this invention: Oxygen vacancies increase surface hydroxyl density: The presence of oxygen vacancies gives the surface of Y-ZrO2 particles more unsaturated coordination sites, which can adsorb more water molecules and form surface hydroxyl groups (-OH), thus giving the membrane a superhydrophilic property with a contact angle ≤30°.
[0033] Oxygen vacancies form ion transport channels: Oxygen vacancies form so-called ion channels within the crystal lattice, which are used for hydroxide ions (OH-). - The rapid transport within the diaphragm provides a channel, significantly reducing the diaphragm's sheet resistivity to ≤0.10 Ω·cm. 2 .
[0034] Solid solution structure enhances alkali resistance: Y 3+ The stable solid solution structure formed by entering the ZrO2 lattice exhibits superior alkali corrosion resistance compared to pure ZrO2. Combined with the physical barrier formed by uniformly dispersed nanoparticles in the polysulfone matrix, it achieves excellent alkali resistance with an alkali loss of ≤0.2% after 30 days.
[0035] Furthermore, the average particle size of the yttrium-doped zirconia nanoparticles is limited to 30 nm to 80 nm. The particle size has a significant impact on the membrane performance: if the particle size is too small, the surface energy of the particles is too high, and they are prone to agglomeration in the polymer matrix, making it difficult to achieve uniform dispersion; if the particle size is too large, the specific surface area of the particles is significantly reduced, and it is impossible to form a sufficiently high-density particle-polymer interface network in the matrix, thereby weakening the ion interfacial transport effect and the protective effect on the matrix. Specifically, the average particle size of the yttrium-doped zirconia nanoparticles is 50 nm. At this particle size, the particles can achieve good dispersion in the polysulfone matrix and form continuous interfacial transport channels.
[0036] The molar content of yttrium doping is limited to 6%–10%; Y 3+ After ions enter the ZrO2 lattice, they replace part of the Zr. 4+Ions introduce oxygen vacancies into the crystal lattice due to charge differences to maintain electroneutrality. These oxygen vacancies are key to improving the hydrophilicity and ion conductivity of the membrane. When the doping concentration is below 6 mol%, the concentration of introduced oxygen vacancies is insufficient, and the performance improvement effect is not obvious. When the doping concentration is above 10 mol%, the excessively high defect concentration may lead to lattice instability, which in turn affects the chemical stability of the material. For example, the doping molar content of yttrium is 8 mol%. At this concentration, sufficient oxygen vacancies can be formed. XPS analysis confirms that the oxygen vacancy concentration on the Y-ZrO2 surface is positively correlated with the surface hydroxyl content. These surface active sites can form hydrogen bond networks with sulfone groups in the polysulfone matrix or carbonyl groups of PVP, giving the originally hydrophobic polysulfone matrix excellent hydrophilicity.
[0037] The addition amount of yttrium-doped zirconia nanoparticles is limited to 50%–70% of the polysulfone matrix mass. The amount of filler added directly affects the pore structure, hydrophilicity, and mechanical properties of the membrane. When the addition amount is less than 50%, the hydrophilic components in the casting solution are insufficient, making it difficult to form an ideal through-finger pore structure during the conversion process. Furthermore, the interfacial network density is insufficient, resulting in limited ion conduction enhancement. When the addition amount is greater than 70%, the viscosity of the casting solution increases sharply, making it difficult to disperse the filler uniformly. Moreover, the flexibility of the membrane after formation is severely reduced, and the membrane becomes brittle and difficult to apply in practice. Specifically, the addition amount of yttrium-doped zirconia nanoparticles is 5.88 g, accounting for 60% of the polysulfone matrix mass (9.8 g).
[0038] The composite membrane with the above composition and structure, after being formed by phase inversion, obtained unique microstructure and performance parameters; Figure 1 The image shows a cross-sectional SEM image of the prepared composite membrane. It can be clearly seen from the image that the membrane cross-section exhibits a through-finger pore structure. The finger pore structure extends from one side surface to the other side surface along the thickness direction of the membrane. The pores have good orientation and almost no sponge-like barrier layer. This structure provides a low-curvature, highly interconnected channel for the transport of ions and water molecules, which is the structural basis for achieving low surface resistivity.
[0039] The average pore size of the diaphragm is limited to 3nm to 5nm. This pore size range can effectively block the passage of hydrogen and oxygen molecules (the molecular dynamic diameter of gases is larger than this range) and prevent cross-permeation of gases, while ensuring sufficient wetting of the electrolyte in the pores and smooth transport of hydroxide ions. The aforementioned diaphragm has an average pore size of 3.79nm as measured by pore size testing, which meets the limitation of the 3nm to 5nm range.
[0040] The porosity of the diaphragm is limited to 60%–70%. Porosity represents the volume ratio of the internal pore space of the diaphragm, which directly affects the alkali absorption rate and ion conduction capacity of the diaphragm. For example, the porosity measured by the wet-dry weight method is 63.7%. The high porosity ensures a high electrolyte holding capacity in the diaphragm, providing a sufficient electrolyte carrier for ion conduction.
[0041] The water contact angle of the diaphragm surface is limited to ≤30°; the contact angle is a direct indicator of the hydrophilicity of the membrane surface. The smaller the contact angle, the better the wettability of the water / electrolyte on the membrane surface, which is more conducive to the rapid wetting of the electrolyte and the transport of ions at the membrane interface; the measured water contact angle of the diaphragm is 29.5° (see...). Figure 4 The results show that the membrane has excellent hydrophilicity. In contrast, the membrane prepared with pure ZrO2 without Y doping has a contact angle of 43.2°, and its hydrophilicity is significantly lower than that of the membrane provided in this application. This confirms the key role of oxygen vacancies introduced by Y doping in improving hydrophilicity.
[0042] The sheet resistivity of the diaphragm in a 30% KOH aqueous solution at 80°C is limited to ≤0.10 Ω·cm. 2 Sheet resistance is a core electrochemical performance indicator for measuring the ion conduction capability of a membrane. The lower the sheet resistance, the smaller the ion conduction resistance, and the lower the electrolysis energy consumption at the same current density. The sheet resistance of the membrane measured under specified test conditions was 0.097 Ω·cm. 2 In contrast, the sheet resistivity of pure ZrO2 is 0.115 Ω·cm. 2 The sheet resistivity of large-particle-size Y-ZrO2 is 0.148 Ω·cm. 2 The diaphragm provided in this embodiment has obvious advantages.
[0043] In a preferred embodiment, the yttrium-doped zirconium oxide nanoparticles have an average particle size of 50 nm, a doping molar content of yttrium of 8%, and a mass of yttrium-doped zirconium oxide nanoparticles that is 60% of the mass of the polysulfone matrix.
[0044] The composite membrane achieves optimal overall performance when the average particle size of the yttrium-doped zirconia nanoparticles is 50 nm, the molar content of yttrium doping is 8%, and the mass of the yttrium-doped zirconia nanoparticles is 60% of the mass of the polysulfone matrix.
[0045] Under these conditions, a particle size of 50 nm enables the Y-ZrO2 particles to achieve optimal dispersion uniformity in the polysulfone matrix (e.g., Figure 3As shown in the EDS surface distribution diagram, Zr and Y elements are uniformly distributed in the film cross-section without obvious agglomeration, while obtaining a sufficiently high specific surface area to construct a high-density interface network; an 8 mol% yttrium doping concentration can form the optimal oxygen vacancy concentration, which can reach the order of about 2 × 10²¹ oxygen vacancy sites / cm³, ensuring sufficient surface hydroxyl sites without causing lattice structure instability due to excessive doping; and a 60% filler addition achieves the best penetration and porosity of the finger pore structure.
[0046] As a preferred embodiment, the composite diaphragm has a mass loss rate of ≤0.2% after being soaked in a 30% KOH aqueous solution at 60°C for 30 days; under the conditions of a current density of 500mA / cm², a temperature of 60°C, and an electrolyte of 30% KOH aqueous solution, the electrolysis voltage is ≤1.70V, and after continuous electrolysis for 375h under the same conditions, the voltage fluctuation is ≤0.1V.
[0047] In this embodiment, regarding alkali loss, the test method involves immersing the diaphragm sample in a 30wt% KOH aqueous solution at a constant temperature of 60℃ for 30 days. After removal, cleaning, drying, and weighing, the percentage of mass loss before and after immersion is calculated. Alkaline electrolysis diaphragms are exposed to a high-temperature, concentrated alkali environment for extended periods during actual operation; therefore, alkali resistance is a key indicator of whether they can meet the requirements for long-term industrial operation. In this embodiment, the diaphragm's mass loss rate after immersion for 30 days under specified conditions is only 0.19%, meeting the requirement of ≤0.2%. In comparison, the alkali loss of pure ZrO2 is 0.29%, while that of large-particle Y-ZrO2 reaches as high as 7.59%. This excellent alkali resistance can be attributed to two aspects: firstly, the Y-ZrO2 particles themselves possess excellent alkali corrosion resistance; secondly, the uniformly dispersed nanoparticles form a dense physical barrier within the polysulfone matrix, effectively blocking OH... - Erosion of the polysulfone backbone.
[0048] Regarding the electrolysis voltage, the test conditions were a current density of 500 mA / cm², an electrolyte of 30 wt% KOH aqueous solution, and an operating temperature of 60°C. The diaphragm prepared in this embodiment had an electrolysis voltage of 1.6997 V under these conditions, which meets the requirement of ≤1.70 V. A lower electrolysis voltage means lower DC power consumption, which is of great significance for reducing the cost of hydrogen production.
[0049] Regarding long-term operational stability, the diaphragm provided in this application operated continuously for 375 hours under conditions of a current density of 500 mA / cm², a temperature of 60℃, and an electrolyte of 30 wt% KOH aqueous solution. The electrolysis voltage remained stable between 1.7V and 1.8V, with voltage fluctuations not exceeding 0.1V, indicating that the diaphragm's performance did not degrade during long-term operation. In contrast, large-particle-size Y-ZrO2, due to its poor alkali resistance, experienced a significant increase in voltage during long-term operation as the matrix was gradually eroded by the alkali solution, leading to pore structure collapse or defect expansion.
[0050] In a preferred embodiment, the composite diaphragm has a bubble point pressure ≥0.6 bar, a tensile strength ≥1.8 MPa, and an elongation at break ≥30%.
[0051] In this embodiment, the bubble point pressure is tested using the bubble point method, which reflects the minimum pressure that gas needs to overcome to penetrate the diaphragm and is a core indicator for measuring the diaphragm's airtightness. The higher the bubble point pressure, the stronger the gas barrier capability of the diaphragm, and the more effectively it can isolate hydrogen and oxygen, preventing the risk of mixed explosion. The diaphragm's bubble point pressure is 0.62 bar, meeting the requirement of ≥0.6 bar. This performance is mainly due to the diaphragm's average pore size of 3.79 nm and its relatively concentrated pore size distribution. It is worth noting that while maintaining a high porosity of 63.7%, a high bubble point pressure can still be achieved, which breaks through the inherent contradiction that high porosity of traditional porous membranes inevitably leads to low airtightness.
[0052] Regarding tensile strength, the tensile strength is 1.9 MPa when the diaphragm thickness is 0.29 mm, meeting the requirement of ≥1.8 MPa. Regarding elongation at break, the diaphragm prepared in this embodiment has an elongation at break of 31.1%, meeting the requirement of ≥30%. The moderate tensile strength and high elongation at break indicate that even with the addition of up to 60% inorganic filler by mass, the diaphragm still possesses good rigidity and toughness, and can withstand the clamping force during the electrolytic cell assembly process and the mechanical stresses such as vibration and thermal expansion during long-term operation. In contrast, the diaphragm using large-particle-size Y-ZrO2, although having a tensile strength as high as 19.7 MPa, has an elongation at break of only 11.7%, exhibiting typical brittle fracture characteristics. It is extremely prone to brittle cracking during actual assembly and use, making it difficult to meet the requirements of industrial applications.
[0053] A method for preparing a composite membrane includes the following steps: S1, dissolve polysulfone resin in N-methylpyrrolidone to obtain a polysulfone solution.
[0054] Specifically: polysulfone resin is dissolved in N-methylpyrrolidone (NMP) to obtain a polysulfone solution; NMP is a good solvent for polysulfone and can fully dissolve solid polysulfone resin to form a uniform and transparent polymer solution, providing a uniform liquid phase environment for subsequent addition of pore-forming agents and inorganic fillers; specifically, 9.8g of polysulfone resin powder is slowly added to 45g of NMP and stirred at room temperature for 4 hours until completely dissolved to obtain a clear and transparent polysulfone solution.
[0055] S2, add polyvinylpyrrolidone to the polysulfone solution, mix and dissolve to obtain a polymer mixed solution.
[0056] Polyvinylpyrrolidone (PVP) was added to a polysulfone solution and mixed to dissolve, resulting in a polymer mixture solution. In this invention, PVP acts as a pore-forming agent and is also a hydrophilic polymer, which can improve the thermodynamic stability of the casting solution and promote rapid solvent-non-solvent exchange during phase transformation, thereby inducing the formation of finger-like pore structures. In addition, PVP also acts as a dispersant, and its macromolecular chains can be adsorbed on the surface of Y-ZrO2 particles, helping the nanoparticles to maintain stable dispersion in the casting solution through steric hindrance. Specifically, 9.8 g of PVP was added and stirred for 2 hours until completely dissolved to form a homogeneous polymer mixture solution.
[0057] S3, add yttrium-doped nano-zirconia powder to the polymer mixture, disperse it evenly and remove bubbles to obtain casting solution.
[0058] Yttrium-doped zirconia nanoparticles were added to the polymer mixture, dispersed evenly, and degassed to obtain a casting solution. The key to this step is achieving uniform dispersion of the yttrium-doped zirconia nanoparticles in the polymer solution. In this embodiment, 5.88 g of yttrium-doped zirconia nanoparticles with an average particle size of 50 nm were added. 3+ After doping with 8 mol% Y-ZrO2 powder, the stirring rate was adjusted to 200 r / min and stirred continuously for 24 hours to ensure that the powder was fully dispersed. Then the casting solution was transferred to a vacuum drying oven and vacuumed at room temperature for 5 minutes to remove the air bubbles mixed in during stirring, resulting in a homogeneous casting solution without air bubbles. If air bubbles remain in the casting solution, they will form macroscopic defects in the subsequent film formation process, which will seriously affect the airtightness and mechanical properties of the diaphragm.
[0059] S4, the casting liquid is scraped onto the substrate to form a liquid film, and then the substrate with the liquid film is immersed in a coagulation bath to carry out phase transformation to obtain a wet film.
[0060] A casting solution is coated onto a substrate to form a liquid film. The substrate with the liquid film is then immersed in a coagulation bath for phase inversion, resulting in a wet film. This step is crucial for forming the membrane's microstructure. The basic principle of the phase inversion method is as follows: after the coated liquid film is immersed in the coagulation bath, the solvent (NMP) in the casting solution and the non-solvent (water) in the coagulation bath undergo bidirectional diffusion exchange. As the solvent is continuously replaced, polysulfone precipitates and solidifies into a film due to the loss of solvent. Due to the combined action of the pore-forming agent PVP and the hydrophilic γ-ZrO2 particles, the non-solvent (water) can rapidly penetrate into the interior of the liquid film, increasing the film thickness. Finger-like protrusions of a polymer-poor phase are formed in the direction of the membrane. These finger-like protrusions grow into the interior of the membrane and eventually penetrate through it, forming finger-like macropores. At the same time, the physical occupancy and rapid gelation of Y-ZrO2 particles restrict the micropore size on the walls of the finger-like pore structure to the nanoscale. The degassed casting solution is poured onto a clean glass plate and coated with a scraper at a uniform speed to control the wet film thickness to about 500 μm. After pre-evaporation in the air for 15 seconds, it is immediately immersed in a coagulation bath. The coagulation bath is a mixture of deionized water and NMP (volume ratio of water:NMP=9:1), at a temperature of 25°C, for 2 hours.
[0061] S5, the wet membrane is washed and dried to obtain the composite diaphragm.
[0062] The wet membrane is washed and dried to obtain a composite membrane. The purpose of washing is to remove the residual solvent NMP and some water-soluble PVP from the wet membrane. After the latter is washed away from the membrane, the original position it occupied forms a pore, which further improves the porosity of the membrane. In this embodiment, after the solidified wet membrane is taken out of the coagulation bath, it is rinsed repeatedly with a large amount of deionized water three times to thoroughly remove residual solvent and impurities. After wiping off the surface moisture with filter paper, it is placed in a vacuum drying oven at 60°C and dried for 24 hours to obtain the final Y-doped nano-zirconia / polysulfone composite alkaline electrolytic water membrane.
[0063] In a preferred embodiment, in step S1, the mass ratio of the polysulfone resin to N-methylpyrrolidone is 1:5 to 10.
[0064] The mass ratio of polysulfone resin to NMP is 1:5 to 10. The amount of solvent affects the viscosity of the casting solution, which in turn affects the operability of the coating process and the solvent-non-solvent exchange rate during the phase inversion process. If the solvent ratio is too low (below 1:5), the viscosity of the casting solution is too high, making it difficult to coat into a liquid film of uniform thickness, and the high viscosity is not conducive to the uniform dispersion of Y-ZrO2 particles. If the solvent ratio is too high (above 1:10), the casting solution is too thin, making it difficult for the liquid film to maintain thickness stability after coating, and when the polymer concentration is too low, the polymer-depleted phase is insufficient to form a complete membrane skeleton during the phase inversion process, resulting in insufficient mechanical strength of the membrane. For example, the amount of polysulfone resin is 9.8g and the amount of NMP is 45g, with a mass ratio of approximately 1:4.6, which is within the range of 1:5 to 10.
[0065] In a preferred embodiment, in step S2, the mass ratio of polyvinylpyrrolidone to polysulfone resin is 0.8 to 1.2:1.
[0066] The mass ratio of PVP to polysulfone resin is 0.8–1.2:1. The amount of PVP directly affects the pore size, porosity, and degree of formation of the finger pore structure of the membrane. If the amount of PVP is too low, the pore-forming effect is insufficient, the formed membrane tends to be dense, the porosity is low, the finger pore structure is not interconnected, and the surface resistivity increases. If the amount of PVP is too high, the membrane pore size is too large, the air tightness decreases, and the high content of water-soluble PVP leaves too many pores after washing, which will weaken the mechanical strength of the membrane. In this embodiment, the amount of PVP is 9.8g, the amount of polysulfone resin is 9.8g, and the mass ratio of the two is 1:1, which is within the range of 0.8–1.2:1.
[0067] In a preferred embodiment, in step S3, the mass ratio of the yttrium-doped nano-zirconia powder to the polysulfone resin is 0.5 to 0.7:1.
[0068] The mass ratio of Y-ZrO2 powder to polysulfone resin is 0.5 to 0.7:1, corresponding to a filler content of 50% to 70% of the polysulfone mass. As mentioned earlier, this ratio range is crucial to ensuring that the membrane possesses high hydrophilicity, high ionic conductivity, good airtightness, and sufficient mechanical strength. In this embodiment, the amount of Y-ZrO2 powder used is 5.88 g, and the amount of polysulfone resin used is 9.8 g, with a mass ratio of 0.6:1, which is within the specified range.
[0069] In a preferred embodiment, in step S4, the coagulation bath is a mixture of deionized water and N-methylpyrrolidone, with a volume ratio of water:NMP=8:2 to 9.5:0.5; the immersion time is 1 to 4 hours.
[0070] The coagulation bath was a mixture of deionized water and N-methylpyrrolidone (NMP) with a volume ratio of water:NMP = 8:2 to 9.5:0.5. Adding a certain proportion of NMP to the coagulation bath aimed to reduce the solvent concentration gradient between the coagulation bath and the casting solution, thus slowing down the solvent-non-solvent exchange rate. If pure water was used entirely as the coagulation bath, the exchange rate would be too fast, causing the liquid film surface to solidify instantaneously, forming a dense skin layer that hinders the continued diffusion of water into the film interior, making it difficult to form a penetrating finger-like pore structure. Furthermore, the skin layer would lead to a sharp increase in sheet resistivity. The presence of an appropriate amount of NMP could slow down the phase transformation rate, allowing the finger-like pore structure sufficient time to grow throughout the entire film thickness. In this embodiment, the volume ratio of water to NMP in the coagulation bath was 9:1, and the immersion time was 2 hours. Under these conditions, the following results were obtained: Figure 1 The ideal through-finger pore structure shown; immersion time in the range of 1h to 4h can ensure sufficient solvent exchange and complete polymer curing.
[0071] Application of a composite membrane in an alkaline water electrolysis hydrogen production device.
[0072] The prepared composite membrane was assembled in the electrolyzer of an alkaline water electrolysis hydrogen production device. Under the conditions of 60°C, 30wt% KOH aqueous solution, and current density of 500mA / cm², the electrolysis voltage was only 1.6997V, and the voltage remained stable for 375 hours of continuous operation. This proves that the composite membrane provided by the present invention has excellent application performance and reliability in alkaline water electrolysis hydrogen production devices.
[0073] Example 1 (YZ50-60) S1: Add 45g of N-methylpyrrolidone (NMP) to a 250mL three-necked flask, and slowly add 9.8g of polysulfone resin (PSF) powder while stirring. Stir at room temperature for 4 hours until completely dissolved to obtain a clear and transparent polysulfone solution; the mass ratio of polysulfone resin to NMP is approximately 1:4.6.
[0074] S2: Add 9.8g of polyvinylpyrrolidone (PVP) to the above polysulfone solution at a stirring speed of 300rpm, and continue stirring for 2h until completely dissolved to form a homogeneous polymer mixture solution; the mass ratio of PVP to polysulfone resin is 1:1.
[0075] S3: Add 5.88g of Y-ZrO2 powder (60% of the PSF mass) to the above mixed solution. The average particle size of this powder is 50nm. 3+ The doping molar concentration was 8 mol%; the stirring rate was adjusted to 200 r / min and stirred continuously for 24 h to uniformly disperse the Y-ZrO2 powder in the polymer solution; then the casting solution was transferred to a vacuum drying oven and vacuum degassed for 5 min at room temperature to obtain a bubble-free casting solution; the mass ratio of Y-ZrO2 powder to polysulfone resin was 0.6:1.
[0076] S4: Pour the fully degassed casting solution onto a clean, flat glass plate, and use a scraper to spread it evenly at a constant speed, controlling the wet film thickness to be approximately 500 μm to form a uniform liquid film; after pre-evaporating in the air for 15 seconds, immediately immerse the entire glass plate with the liquid film into a coagulation bath; the coagulation bath is a mixture of deionized water and N-methylpyrrolidone, with a volume ratio of water:NMP=9:1, and a temperature of 25℃; maintain the immersion state for 2 hours to allow the solvent and non-solvent to exchange, and the polymer to precipitate out, forming a wet composite membrane with a microporous structure.
[0077] S5: Carefully remove the solidified wet membrane from the coagulation bath and rinse the membrane surface three times with plenty of deionized water to thoroughly remove residual solvent and impurities; wipe off the surface moisture with filter paper and dry the sample in a vacuum drying oven at 60℃ for 24 hours to obtain the final Y-doped nano-zirconia / polysulfone composite alkaline water electrolysis membrane, named YZ50-60.
[0078] Comparative Example 1 (Z50-60) The difference from Example 1 is that in step S3, 5.88g of pure nano ZrO2 powder (average particle size 50nm, no Y element doping) is added instead of Y-ZrO2 powder; the remaining steps and conditions are exactly the same as in Example 1.
[0079] Comparative Example 2 (YZ200-60) The difference from Example 1 is that 5.88g of large-particle-size γ-ZrO2 powder with a particle size range of 100-200nm was added in step S3. 3+ The doping concentration remained at 8 mol%; the remaining steps and conditions were exactly the same as in Example 1.
[0080] The diaphragms obtained in the above embodiments and comparative examples were subjected to structural characterization and performance testing.
[0081] Figure 1 The image shows a cross-sectional SEM image of the composite membrane prepared in Example 1. The image clearly shows that the membrane cross-section exhibits a typical through-finger pore structure, with large finger pores extending from the upper surface to the lower surface of the membrane. The pores have good orientation and almost no sponge-like obstruction layer. This structure provides a low-curvature, highly interconnected transport channel for ions and water molecules, which is the structural basis for achieving low surface resistivity. The average pore size of Example 1 was measured to be 3.79 nm, and the porosity was 63.7%. In contrast, although Comparative Example 1 also formed a finger pore structure, its pore penetration and uniformity were slightly inferior to Example 1. Comparative Example 2, due to the use of large-diameter Y-ZrO2 particles, exhibited a different interaction mode between the particles and the polymer during the phase transformation, resulting in a relatively loose mixed structure of sponge-like and finger pore structures with a thicker dense skin layer.
[0082] Figure 2 The image shows a planar SEM image of the composite membrane prepared in Example 1. As can be seen from the image, the membrane surface is dense and flat, with no obvious particle agglomeration or macroscopic defects. The dense surface skin helps to improve the gas barrier capacity of the membrane.
[0083] Figure 3The EDS elemental distribution diagram of the composite membrane prepared in Example 1 shows the distribution of Zr and Y elements in the membrane cross-section. As can be seen from the figure, Zr and Y elements are uniformly dispersed inside the membrane without obvious agglomeration areas, proving that Y-ZrO2 particles achieve good dispersion in the polysulfone matrix. This is crucial for the uniformity and reliability of the overall performance of the membrane.
[0084] Figure 4 The water contact angle test diagram is shown for the composite membrane prepared in Example 1; the contact angle of Example 1 was measured to be 29.5°; the water contact angles of the membranes of Example 1 and Comparative Examples 1-2 were measured, and the results are shown in the table below:
[0085] As can be seen from the table above, the contact angles of the three examples, from smallest to largest, are: Example 1 (29.5°) < Comparative Example 1 (43.2°) < Comparative Example 2 (54.5°). This comparison fully demonstrates that the oxygen vacancies introduced by Y element doping significantly increase the hydroxyl density on the surface of zirconium oxide particles, thereby greatly improving the hydrophilicity of the membrane. Y doping reduces the contact angle from 43.2° to 29.5°, a decrease of 32%. At the same time, small-diameter particles have a larger specific surface area, which can provide more surface hydroxyl sites, further improving hydrophilicity. Comparative Example 2 uses large-diameter Y-ZrO2. Although the particles themselves also have oxygen vacancies, the total amount of surface hydroxyl is limited due to the significant reduction in specific surface area. In addition, the large particle size causes changes in the surface roughness of the membrane, resulting in the largest contact angle.
[0086] The membrane porosity was determined by the wet-dry weight method, and the alkali absorption rate was determined by the gravimetric method (soaking in 30wt% KOH solution for 4 hours). The results are shown in the table below:
[0087] Data shows that the porosities of Example 1 and Comparative Example 1 are quite similar, both above 62%, indicating that whether or not Y doping is used has little effect on porosity, which is mainly determined by the amount of filler added and the phase transformation process parameters. However, the porosity of Comparative Example 2 is only 50.7%, significantly lower than the former two, indicating that large-diameter particles are not conducive to forming a high-porosity through-pore structure. Comparative Example 2 has the highest alkali absorption rate (212.7%), but this is because its membrane structure is loose and has large pores and defects, resulting in a large amount of alkali being absorbed but not effectively utilized, and does not represent excellent ion conduction performance.
[0088] The sheet resistance was measured using AC impedance spectroscopy at 30 wt% KOH and 80 °C. The sheet resistance of Example 1 was 0.097 Ω·cm²; that of Comparative Example 1 was 0.115 Ω·cm²; and that of Comparative Example 2 was 0.148 Ω·cm². Example 1 had the lowest sheet resistance, which was about 48% lower than that of the pure PSU membrane. This was due to the oxygen vacancies introduced by Y doping, which increased the surface hydroxyl density and ion conduction sites, as well as the high-density interface network formed by the 50 nm small-diameter particles and the low mass transfer resistance of the penetrating finger-like pore structure. Comparative Example 1, due to the lack of oxygen vacancies, had weaker hydrophilicity and surface conductivity, resulting in a higher sheet resistance than Example 1. Comparative Example 2 used large-diameter Y-ZrO2, which significantly reduced the specific surface area and interface density, resulting in a poorer ion conduction path and the highest sheet resistance.
[0089] The air tightness of the diaphragm was tested using the bubble point method, and the results are shown in the table below:
[0090] The bubble point pressures of Example 1 and Comparative Example 1 are similar, both around 0.6 bar. It is worth noting that Example 1, with a porosity as high as 63.7%, can still achieve a bubble point pressure of 0.62 bar, which is due to its average pore size of 3.79 nm and concentrated pore size distribution. The small pore size ensures gas barrier capability, and the high porosity ensures ion conduction capability. The synergistic optimization of small pore size and high porosity breaks through the contradiction between the airtightness and conductivity of traditional porous membranes from a structural point of view. Although Comparative Example 2 has a bubble point pressure as high as 1.02 bar, its porosity is only 50.7%, and its surface resistivity is the largest. It has not achieved a unity of conductivity and airtightness.
[0091] Tensile strength tests were conducted on a 1.4cm × 4cm strip of composite diaphragm, and the results are shown in the table below:
[0092] Example 1, even with a filler content of up to 60% inorganic filler, still exhibits good tensile strength and elongation at break, demonstrating a balance of rigidity and flexibility in its mechanical properties. This allows it to meet the clamping force requirements during electrolytic cell assembly and the mechanical stress tests during long-term operation. Comparative Example 1 has slightly lower tensile strength but the highest elongation at break and the best flexibility. Comparative Example 2, although possessing extremely high tensile strength, has an elongation at break of only 11.7%, exhibiting typical brittle material characteristics. It is prone to brittle cracking during assembly and operation, making it difficult to meet the requirements of industrial applications.
[0093] The diaphragm was immersed in a 30 wt% KOH aqueous solution at 60°C for 30 days, and the mass loss rate was measured to evaluate its alkali resistance stability. The alkali loss in Example 1 was 0.19%, in Comparative Example 1 it was 0.29%, and in Comparative Example 2 it was 7.59%. Example 1 showed the best alkali resistance stability. The mechanism is that the uniformly dispersed small-diameter Y-ZrO2 nanoparticles formed a dense physical barrier in the polysulfone matrix, effectively blocking OH. - The alkali loss of Y-ZrO2 is slightly higher than that of Example 1 because it uses pure ZrO2 (without Y doping), which has a different chemical state on the particle surface and a slightly weaker interfacial bonding and barrier effect with the matrix. The alkali loss of Example 2 is slightly higher than that of Example 1 because it uses large-particle-size Y-ZrO2, which easily forms interfacial defects and voids around the particles, providing channels for alkali penetration. As a result, the alkali directly attacks the polysulfone matrix, and the alkali loss after 30 days is as high as 7.59%, indicating extremely poor alkali resistance.
[0094] Electrolysis tests were conducted at 60°C, 30 wt% KOH aqueous solution, and a current density of 500 mA / cm². The electrolysis voltage of Example 1 was 1.6997 V; the electrolysis voltage of Comparative Example 1 was 1.752 V; and the electrolysis voltage of Comparative Example 2 was 1.801 V. Example 1 had the lowest electrolysis voltage and the lowest energy consumption. Compared with Comparative Example 1, the electrolysis voltage of Example 1 decreased by approximately 0.052 V, which was mainly attributed to the oxygen vacancies introduced by Y doping, which increased the surface hydroxyl density and ion conduction sites, thereby reducing the surface resistivity. Compared with Comparative Example 2, the electrolysis voltage of Example 1 decreased by approximately 0.101 V, which, in addition to the contribution of Y doping, also benefited from the high-density interface network formed by small-diameter particles and the low mass transfer resistance of the penetrating finger-like pore structure.
[0095] The membrane prepared in Example 1 was subjected to continuous electrolysis testing at 60°C, 30wt% KOH, and 500mA / cm². The results showed that the membrane could operate stably for more than 375 hours, with the electrolysis voltage remaining stable between 1.7V and 1.8V, and voltage fluctuations ≤0.1V, without any performance degradation. This fully demonstrates that the composite membrane of Example 1 has excellent long-term operational reliability in alkaline water electrolysis hydrogen production devices and meets the intensity requirements of alkaline water electrolysis.
[0096] The performance comparison of each embodiment and comparative example is summarized in the table below:
[0097] As can be seen from the table above, Example 1 demonstrates excellent performance in key performance indicators such as hydrophilicity, ion conductivity, airtightness, alkali resistance, electrolytic performance, and long-term operational stability. Its overall performance far exceeds that of the comparative examples, proving the effectiveness and inventiveness of the present invention through the oxygen vacancy engineering and particle size synergistic control strategy.
[0098] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite diaphragm for alkaline water electrolysis, characterized in that, include: Polysulfone matrix; Yttrium-doped zirconium oxide nanoparticles dispersed in the polysulfone matrix; the yttrium element in the yttrium-doped zirconium oxide nanoparticles is in the form of trivalent yttrium ions (Y). 3+ Form doping is introduced into the zirconium dioxide lattice, replacing some of the tetravalent Zr in the zirconium dioxide lattice. 4+ The ions form a solid solution, wherein the average particle size of the yttrium-doped zirconium oxide nanoparticles is 30 nm to 80 nm, wherein the molar content of yttrium is 6% to 10%, and the mass of the yttrium-doped zirconium oxide nanoparticles is 50% to 70% of the mass of the polysulfone matrix; The composite membrane has a finger-like pore structure, with the finger-like pores extending throughout the membrane thickness direction. The average pore size of the composite membrane is 3nm–5nm, the porosity is 60%–70%, the surface water contact angle is ≤30°, and the surface resistivity in a 30% (w / w) KOH aqueous solution at 80°C is ≤0.10 Ω·cm. 2 ; The yttrium-doped zirconium oxide nanoparticles have an average particle size of 50 nm, a yttrium molar content of 8%, and a mass of 60% of the mass of the polysulfone matrix. The composite diaphragm exhibits a mass loss rate of ≤0.2% after immersion in a 30% KOH aqueous solution at 60°C for 30 days. Under the conditions of a current density of 500 mA / cm², a temperature of 60℃, and an electrolyte of 30% KOH aqueous solution, the electrolysis voltage is ≤1.70V, and after continuous electrolysis for 375h under the same conditions, the voltage fluctuation is ≤0.1V. The composite diaphragm has a bubble point pressure ≥0.6 bar, tensile strength ≥1.8 MPa, and elongation at break ≥30%.
2. A method for preparing the composite diaphragm according to claim 1, characterized in that, Includes the following steps: S1, dissolve polysulfone resin in N-methylpyrrolidone to obtain a polysulfone solution; S2, add polyvinylpyrrolidone to the polysulfone solution, mix and dissolve to obtain a polymer mixed solution; S3, add yttrium-doped nano-zirconia powder to the polymer mixture, disperse it evenly and remove bubbles to obtain a casting solution; S4, the casting liquid is scraped onto the substrate to form a liquid film, and then the substrate with the liquid film is immersed in a coagulation bath to carry out phase transformation to obtain a wet film; S5, the wet membrane is washed and dried to obtain the composite diaphragm.
3. The method according to claim 2, characterized in that, In step S1, the mass ratio of the polysulfone resin to N-methylpyrrolidone is 1:5 to 10.
4. The method according to claim 2, characterized in that, In step S2, the mass ratio of polyvinylpyrrolidone to polysulfone resin is 0.8 to 1.2:
1.
5. The method according to claim 2, characterized in that, In step S3, the mass ratio of the yttrium-doped nano-zirconia powder to the polysulfone resin is 0.5 to 0.7:
1.
6. The method according to claim 2, characterized in that, In step S4, the coagulation bath is a mixture of deionized water and N-methylpyrrolidone, with a volume ratio of water:NMP=8:2 to 9.5:0.5; the immersion time is 1h to 4h.
7. The application of the composite membrane according to claim 1 in an alkaline water electrolysis hydrogen production device.
